Critical technologies and geology-engineering integration practices for deep CBM production in the Yanchuannan CBM field - Zhenlong CHEN; Yunhai WANG; Xiao LIU; Bin CUI; Song YANG; Xin LI; Qilong FANG (Meitian dizhi yu kantan)
Objective and Methods This study introduces the adjustments for coalbed methane (CBM) production in the Yanchuannan CBM field‒the first deep CBM field in China. Deep CBM production in this CBM field faces challenges including strong heterogeneity of reservoirs, single arrangement mode of production well patterns, low applicability of conventional hydraulic fracturing, excessively long conventional production cycles, and a high proportion of inefficient wells. To address these challenges, a production capacity construction model for efficient deep CBM production of the field was developed through in-depth geology-engineering integration. Results and ConclusionsThe results indicate that the production capacity construction process of the Yanchuannan CBM field has undergone three stages: large-scale production capacity construction, addressing technological challenges, and technological innovations and their popularization. [Results and Conclusions] The following achievements were obtained: (1) The geological understanding of four critical indicators for the selection of optimal geological-engineering “sweet spots” and efficient CBM production. (2) The concept of fracturing through effective propping and key supporting technologies for reservoir stimulation. (3) The optimal and fast production technologies characterized by four stages, three pressures, and three aspects of control. Based on these achievements, the average cycle for acquiring gas shows was shortened from 240 d to 30 d, and the single-well production was significantly enhanced, with the daily gas production of directional and horizontal wells reaching 2.0×104 m3 and 6.5×104 m3, respectively. The deep CBM reservoirs in the Yanchuannan CBM field exhibit strong heterogeneity, causing difficulties with effective production. Given this, the work philosophy that consolidates overall deployment, implementation in batches, integrated assessment and construction, and rolling production capacity construction was developed for production capacity construction. Adhering to this work philosophy, the production capacity construction was performed through continuous assessment and adjustment of geological-engineering sweet spots and timely optimization of production schemes to effectively avoid the co-occurrence of a substantial number of inefficient wells. This increased the fulfillment rate of production capacity from the initial 84% to 100%, suggesting significantly enhanced economic effects. Based on the concept of geology-engineering integration and the full life cycle of gas reservoir development that consists of well emplacement, well drilling and completion, reservoir stimulation, well tests and production, and gathering, transportation, and processing, the following outcomes were obtained: (1) Rational well spacing that matches reserves, well patterns, and fracture networks, increasing single-well producing reserves by 30% to 50%. (2) The optimal well drilling and completion technology focusing on speed increase and cost reduction, improving the drilling speed by 34%. (3) The low-pressure gathering and transportation technology involving high- and low-pressure gathering and transportation, three-stage pressurization, and inter-station connection, reducing the platform investment by 10.8% and the land use by 20%. The geology-engineering integration practices in the Yanchuannan CBM field provide technical support for the deep CBM industry, holding great demonstration and promotion significance.